Penerapan Supervisi Kolaboratif untuk Meningkatkan Kompetensi Profesional Guru dalam Mengembangkan Bahan Ajar - Jasmin, Jasmin (Ridwan Institute, 2021)
The research objectives are to describe: 1) the development of a collaborative supervision process to improve teacher professional competence in developing teaching materials; 2) increasing the professional competence of teachers in SMA Negeri 1 Bunyu after applying the collaborative supervision approach. This research is a qualitative research, with aapproach phenomenological qualitative descriptive. Qualitative data were obtained from observation sheets and interviews. Meanwhile, the quantitative data were obtained from the test results. The test consists of two cycles. Data were analyzed using Kemmis and Mc. Taggart which is a development model of Kurt Lewin's model. It is said that, because in a cycle consists of four components, the four components include: (1) planning, (2) action / action, (3) observation, and (4) reflection. The benefits of this research can be used as a reference to serve as an alternative approach to supervision to improve teacher competence and school quality as a result of increasing the quality of teacher work in carrying out their professional duties.